Analisis Hubungan Antara Beban Kerja Dengan Stress Kerja Pada Kurir: Systematic Literature Review - Oktavia Ika Nur Winda Satriani; Puspikawati, Septa Indra; Wahyudiono, Yustinus Denny Ardyanto (Universitas Airlangga, 2025)
Background: The rapid growth of e-commerce in Indonesia has increased the demand for delivery services, primarily from online buyers and sellers. This surge elevates couriers' workload, leading to prolonged work hours and unstable conditions (extreme weather exposure, and inconsistent delivery targets), which contribute to stress. Persistent work stress negatively affects productivity, quality of life, and physical and mental health. Objectives: To analyze the relationship between workload and job stress in couriers, and determine the relationship between external and internal factors of work stress in couriers. Methods: This study employed a literature review method, utilizing national and international articles that met the inclusion and exclusion criteria. The selected journal articles were from research published in the last five years (2020-2025) and were sourced from databases such as Google Scholar, PubMed, and ScienceDirect. The data search strategy applied the PICO method (Population, Intervention, Comparison, and Outcomes) using keywords combined with Boolean operators (AND, OR, NOT) to refine or expand the search. Results: The results of data search through the screening stage found a total of seven articles, namely four national articles and three international articles. The results of the search for these seven articles prove that as many as 85.7% indicate a relationship between workload and work stress in couriers. Conclusions: Based on the comparative analysis of the number of articles found and selected, there is a relationship between workload and work stress in couriers. External factors of high work demands with long working hours can cause work stress which can interfere with workers' work.